2018
DOI: 10.1186/s40104-018-0294-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary arginine to lysine ratios on productive performance, meat quality, plasma and muscle metabolomics profile in fast-growing broiler chickens

Abstract: BackgroundDue to the important functions of arginine in poultry, it should be questioned whether the currently adopted dietary Arg:Lys ratios are sufficient to meet the modern broiler requirement in arginine. The present study aimed, therefore, to evaluate the effects of the dietary supplementation of L-arginine in a commercial broiler diet on productive performance, breast meat quality attributes, incidence and severity of breast muscle myopathies and foot pad dermatitis (FPD), and plasma and muscle metabolom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
50
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 52 publications
8
50
1
1
Order By: Relevance
“…The average feed conversion of a 4week-old broilers in this study ranged from 1.55 to 1.66. The results of the present study were almost the same as those reported by Zampiga et al (2018), where the average feed conversion of broiler feed conversion was between 1.494 and 1.524 for 33 days.…”
Section: Resultssupporting
confidence: 90%
“…The average feed conversion of a 4week-old broilers in this study ranged from 1.55 to 1.66. The results of the present study were almost the same as those reported by Zampiga et al (2018), where the average feed conversion of broiler feed conversion was between 1.494 and 1.524 for 33 days.…”
Section: Resultssupporting
confidence: 90%
“…According to the findings of Rezaei et al (2004) who stated the national research council (NRC) requirement for lysine is too low for the period of 3 to 6 weeks of age and had absence of significant result on mortality of birds. Similar results were mentioned by Zampiga et al (2018) who showed that there was no significant effect on the mortality percentage of chicks supplemented with dietary arginine to lysine in each feeding phase as well as in the overall period of the trial.…”
Section: Mortalitysupporting
confidence: 87%
“…Higher dietary Arg levels (Arg:Lys ratio: + 30% in respect to the current recommendations) may play a role in reducing breast muscle abnormalities in broilers by increasing nitric oxide production, vascularization, and oxygenation and even helping with creatine metabolism (Zampiga et al, 2019). In contrast, Zampiga et al (2018) observed that slight Arg increases were not adequate to mitigate myopathies. However, in practical terms of feed formulation, higher Arg:Lys ratios mean either higher dietary protein content or considerable supplementation of crystalline Arg.…”
Section: Gaa and Creatine In Muscle Disordersmentioning
confidence: 93%